PERANGKAT LUNAK BANTU PENDETEKSI KONEKSI KABEL STP MENGGUNAKAN VISUAL BASIC - Wijaya, Merry; Purwanto, Timur Dali (Universitas Bina Darma, 2014)
On the creation of a computer network requires a media liaison (connector) and STP cable (Shielded Twisted Pair) to connect one computer and another computer. And to determine if the STP cable is in good condition or damaged need a tool that can detect damage to the cable. Detection tool or LAN STP cable tester on the market usually only test the connection only, and therefore is expected to manufacture this tool is not only able to test the connection, but also can detect the polarity of each STP cable on the network, so for beginners who just found out about wiring can better understand it and to facilitate network administrators to detect damage to the STP cable.